Dunia Islam Abad 19: Penetrasi Kolonial Barat - Maulana Yusuf (Faculty of Sharia, Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, Indonesia, 2011)
The world of islam in umayyah and absiyyah dynasties was in the world in the hand of a single leader, however since the 10th century raised a new development by the presence of new leaders who was appointed buy khalifah as the vice leader in some islamic world who were finally became the independent leader. Also, there were some leaders who againts the abasiyyah kahlifah and declared the mselves the conguers of islamic world, such as umayyag dynasti is spain, fatimiyah dynasti in the north africa, and the establishments of three well-know kingdom: turki usmani, safawi, and mughal in india with its own glory and victory. Unfotunstely, the victory of islam began to lose its glow in the 19th century when the islamic world was politically collaps and became worse as accordance with the raise of west from the dark ages into light which support freedom and science that contrast t=with the islamic world in colonialism.